Job polarization in Europe: Evidence from Central and Eastern European countries - Dennis Nchor; Petr Rozmahel (DANUBE: Law, Economics and Social Issues Review, 2020)
Job polarization simply refers to the decline or disappearance of employment in middle skill occupations. Recent literature focuses on this phenomenon as a source of rising income inequality in countries. The hypothesis is that growth in employment over the last decades has favoured jobs at the low and high skill occupations with declines in employment shares in the middle of the distribution. First, this paper seeks to investigate whether labour polarization occurs in Central and Eastern European countries. Secondly, the paper assesses the role of technology on employment in the Central and Eastern European countries. Using employment shares and a cointegrated panel autoregressive distributed lag model, the paper presents comprehensive results on labour polarization and the impact of technology on employment in the labour markets of the Central and Eastern European countries. The results show positive impact of technology on high skill employment while negative on low and middle skill employment in the long-run. The study finds that though middle skill employment shares declined, there is no clear case of a U-shape employment distribution to indicate labour polarization.
Keywords: 330; Employment; Skill; Polarization; Routine; Labour